Manajemen Sarana dan Prasarana di SMP Negeri 255 Jakarta - Angga Harizki; Wahyu Sri Ambar Arum; Neti Karnati (Program Studi Manajemen Pendidikan, 2017)
The research aimed to identify and obtain an overview of the maintenance andinventory of educational facilities. This research was conducted in in SMP Negeri 255 onMay 2015 through June 2016. The research used a qualitative approach with descriptivemethods. Data was collected through interviews, observation and documentation. Sourcedata from this study came from key informants that the vice principal fields ofinfrastructure, while supporting informant I is treasurer of goods and informants II is theprincipal. Results from the study showed that (1) Mechanical maintenance of educationalfacilities that do SMP Negeri 255 Jakarta include awareness, understanding, organizing,implementation and data collection. Problems that occur in the technical maintenance ofeducational facilities is the lack of a clear division of labor, funding needs due to latedisbursement of BOS and BOP, and difficulty to obtain experts. (2) Procedures inventoryof educational facilities was conducted on the recording, coding and inventoryevaluation. Problems that occur in the inventory procedure for school infrastructure isoften the goods delivered are not in accordance with the required specifications of theschool, so that has caused delays in the process of recording goods.